Reaksi Pasar Terhadap Peristiwa Pengumuman Hasil Hitung Cepat Dan Hitung Manual Kpu Pada Pemilihan Umum Presiden 2024 - Iman Ahmad Syahbandi; Syahbandi; Anggraini Syahputri; Anwar Azazi; Uray Ndaru Mustika (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This research investigates how the Indonesian capital market reacts to a major political milestone the release of quick count and official manual count results from the 2024 Presidential Election. The study focuses on a sample of highly liquid equities included in the KOMPAS100 Index. The investigation assesses anomalous returns (AR) and trading volume activity (TVA) over two different windows before and after the announcements using a quantitative approach using an event study methodology. The Indonesia Stock Exchange (IDX) provided the data, which were then evaluated using paired sample t-tests. The findings imply that there was no statistically significant change in abnormal returns or trading activity as a result of the official count announcements or the rapid count. Nonetheless, notable differences emerged when comparing the pre-event periods of both announcements, with TVA showing substantial movement after both events. These findings imply that the capital market tends to express reactions through fluctuations in trading activity rather than price volatility, particularly within the segment of highly liquid stocks. Therefore, while large-scale political events like presidential elections may not significantly alter returns, they do influence trading behaviors.